E-CERTIFICATES IN SCHOOLS TO IMPROVE ADMINISTRATIVE EFFECIENCY IN THE SOCIETY 5.0 ERA - Muhtar, Arista Nur Azizah (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2025)
The era of Society 5.0 has brought many changes in various aspects of life, including in the management of educational administration, namely certificate. E-certificate or electronic certificate are digital documents that serve as proof of graduation. This study uses a literature review method, where the researcher collects information from sources such as books, articles, the internet, and other sources related to the title. Through his study, it can be seen that the use of technology in e-certificate management is supported by several technologies, such as blockchain, QR codes, the web, electronic signatures, and cloud storage. E-ijazah as a form of administrative digitization presents several important benefits, including, 1) operational efficiency, 2) security and accountability, and 3) accountability. In addition, the implementation of e-certificates has advantages as well as challenges that must be faced. The advantages are security and authenticity, transparency and accountability, and process efficiency. Meanwhile, the challenges faced are a) infrastructure readiness, b) compliance with regulations, and c) adoption by stakeholders. Keywords: E-certificate; Administrative Efficiency; Society 5.0   Abstrak Era Society 5.0 membawa banyak perubahan dalam berbagai aspek kehidupan termasuk dalam pengelolaan administrasi pendidikan yaitu ijazah. E-ijazah atau ijazah elektronik merupakan dokumen bukti kelulusan yang disajikan secara digital. Penelitian ini menggunakan metode studi kepustakaan dimana peneliti mengumpulkan informasi dari sumber bacaan seperti buku, artikel, internet, maupun sumber informasi lainnya yang berkaitan dengan judul. Melalui penelitian ini dapat diketahui bahwa, pemanfaatan teknologi dalam pengelolaan e-ijazah didukung oleh beberapa teknologi seperti blockchain, QR code, web, tanda tangan elektronik, maupun penyimpanan cloud. E-ijazah sebagai bentuk digitalisasi administrasi menawarkan beberapa manfaat penting, yaitu 1) efisiensi operasional, 2) keamanan dan akuntabilitas, dan 3) akuntabilitas. Selain itu, implementasi e-ijazah memiliki keunggulan sekaligus tantangan yang harus dihadapi. Keunggulan tersebut yaitu, keamanan dan keaslian, transparansi dan akuntabilitas, serta efisiensi proses. Sedangkan tantangan yang dihadapi yaitu, a) kesiapan infrastruktur, b) kepatuhan terhadap regulasi, dan c) adopsi dari stakeholder. Keywords: E-ijazah; Efisiensi Administrasi; Society 5.0